Improvement in the quality of patient notes: A report of a closed loop audit quality improvement project at a neurosurgical department in Pakistan. - Ashraf , Mohammad; Shahzad Hussain, Syed; Ahmad Kamboh, Usman; Mehreen Mehboob; Saman Shahid; Naveed Ashraf (Journal of the Pakistan Medical Association, 2021)
https://jpma.org.pk/article-details/10679?article_id=10679